How can we improve the use of essential evidence-based interventions? - Belizán, José M (Reprod Health, 2014)
Between 250,000-280,000 women die worldwide during pregnancy and childbirth each year and children in low- and middle-income countries are 56 times more likely to die before the age of 5 than children in high-income countries. This Editorial discusses the publishing of a supplement within Reproductive Health titled Essential interventions for maternal, newborn and child health which aims to provide a scientific basis to the recommended interventions along with implementation strategies and proposed packages of care.